Freezing of water droplets colliding with kaolinite particles - E. A. Svensson; C. Delval; P. von Hessberg; M. S. Johnson; J. B. C. Pettersson (Atmospheric Chemistry and Physics, 2009)
Contact freezing of single supercooled water droplets colliding with kaolinite dust particles has been investigated. The experiments were performed with droplets levitated in an electrodynamic balance at temperatures from 240 to 268 K. Under relatively dry conditions (when no water vapor was added) freezing was observed to occur below 249 K, while a freezing threshold of 267 K was observed when water vapor was added to the air in the chamber. The effect of relative humidity is attributed to an influence on the contact freezing process for the kaolinite-water droplet system, and it is not related to the lifetime of the droplets in the electrodynamic balance. Freezing probabilities per collision were derived assuming that collisions at the lowest temperature employed had a probability of unity. Mechanisms for contact freezing are briefly discussed.